EFEKTIVITAS PEMBELAJARAN MEMBACA AL-QUR'AN METODE AL-HUSNA DI PONDOK TARBIYATUL QURAN JETAK, WONOREJO, GONDANGREJO, KARANGANYAR - Agus Setyawan; Siti Rokhimah (MAMBA'UL 'ULUM, 2023)
Reading Al Quran is a must for Muslims. However, it is very unfortunate that 65% of Indonesia's population cannot read the Qur’an. Al-Qur'an illiteracy must be eradicated immediately, and this is our collective responsibility. One way to eradicate illiteracy in the Qur’an is to teach students as early as possible. The purpose of this study is to determine the effectiveness of learning to read the Qur’an using the Al-Husna method for the first grade students at Pondok Tarbiyatul Qur'an Karanganyar, and the factors that support the effectiveness of learning to read the Qur’an using the Al-Husna method. This study used descriptive quantitative research methods. Data collection was carried out by observation, interviews, documentation. The subjects of this study were the first grade students at Pondok Tarbiyatul Qur'an (PTQ) Cahaya Nusantara, Jetak Hamlet, Wonorejo Village, Gondangrejo District, Karanganyar Regency. The results of this study show that learning to read the Qur’an using the AlHusna method is effective in improving the ability to read the Qur’an for the first grade students at Pondok Tarbiyatul Qur'an Cahaya Nusantara Jetak, Wonorejo, Gondangrejo, Karanganyar. There are 21 students who have completed the Al-Husna learning method within 3 to 4 months and can read the Al-Qur'an. The factors that support the effectiveness of learning to read the Qur’an using the Al-Husna method, namely, the sincerity of students in learning and teachers in teaching, increasing flight hours, concentration, applying learning designated by the al-Husna method, competent teachers, adequate facilities and infrastructure, cooperation between teachers and parents, and always praying to gain useful knowledge.